Prelacteal Feeds in China - Tang, Li; Hewitt, Katie; Yu, Chuan (Bentham Science Publishers Ltd., 2012)
The custom of providing prelacteal feeds is a long-held tradition throughout many parts of China. Prelacteal feeds are not recommended because they can interfere with the establishment of breastfeeding, increase the risk of infection and change the composition of the human microbiome. The objective of this paper is to review the rate of offering prelacteal feeds in different areas in China and the influence this custom has on breastfeeding outcomes. Electronic databases were systematically searched to identify studies reporting on prelacteal feeds in China. In total eight papers (three retrospective cohort studies, one prospective cohort study, one case-control study and three cross-sectional studies) published in the Chinese language and six papers (one Systematic Literature Review (SLR), four prospective cohort studies and one cross-sectional study) published in the English language were retrieved. The prevalence of prelacteal feeding varies widely in China. The highest rates are seen in Shandong Province in Eastern China, with as many as 72.4% of infants receiving a prelacteal feed before the initiation of breastfeeding. Xinjiang- Province in the west of China reported a lower prevalence of prelacteal feeding; with 23%, 2% and 6% of infants receiving water, cow's milk and solid food, respectively, before discharge from hospital. In comparison to western developed countries prelacteal feeding rates in China were found to be substantially higher. Five out of the seven studies that measured the effect of prelacteal feeds on breastfeeding outcomes found that prelacteal feeding was associated with reduced breastfeeding duration. Due to the potentially deleterious effect of prelacteal feeding on breastfeeding, every effort should be made to reduce prelacteal feeding throughout China.